Principles of Service Design in The Service Activities of The Health Resort Sector - Artur MAIK; Angelika PIENIAS (Communications of International Proceedings, 2022)
The purpose of this study is primarily to outline the principles of using service design in the services offered by the spa sector. The health resort sector is a difficult and demanding sector, but at the same time very interesting in terms of the services offered and the possibility of conducting research (very few studies focused on the health resort sector). The author of this study, based on studying Polish and foreign literature in the field of design thinking and organizational design, noticed a gap in the form of a lack of information on service design in healthcare entities, thanks to which he chose this direction of scientific development. This review is important compared to all available research, as it concerns a sector that has not been studied in this context so far. The article is illustrative in nature and is an attempt to organize the content in this regard. The manuscript was created on the basis of literature studies - it is theoretical in nature. Through literature studies, an attempt was made to identify five basic principles of service design and relate them to the reality of enterprises. The study presents the design thinking method, and also indicates how service design can be related to the health resort sector and entities operating in it.
Keywords: Service - Design - Management – Quality